Viscera Characteristics of MSTN-Edited Heterozygous Pigs - Pei, Yangli; Fan, Ziyao; Song, Yuxin; Chen, Chujie; Mu, Yulian; Li, Bugao; Feng, Zheng; Li, Hua; Li, Kui (Frontiers in Genetics, 2022)
Myostatin (MSTN) is a protein that negatively regulates growth of skeletal muscle, and inactivation of MSTN improves the mass of skeletal muscle. Our previous work found that MSTN+/− pigs have higher muscle depth and lower fat depth compared to wild type without any developmental problems. Therefore, MSTN-edited pigs are most likely to appear as heterozygotes in the potential future market, but the characteristics of organs in digestive and reproductive system of pigs with MSTN gene editing remains unclear. Here, we investigated the histological of the organs in the digestive system and reproductive system in MSTN gene heterozygotes at adult stages. The length of intestine was further compared between adult heterozygous and wild type pigs. We found no significant differences in histomorphology of organs, including heart, duodenum, jejunum, ileum, cecum, colon, testis, epididymis, ovaries, oviducts and uterus, between individuals from two genotypes. Moreover, there was no significant difference in the average length of intestine in adult pigs. Our data provide a reference for further clarifying the applications of MSTN gene edited pigs.